Case Report: Nursing Care After Cesarean Section in S P1A0 UK 38 Weeks With Indications Of Presbo Primitua - Feriyantika; Dwi Sri Handayani; Diah Nur Anisa (International Journal of Health Engineering and Technology, 2026)
Cesarean section (CS) is a surgical procedure to deliver a fetus through an incision in the abdominal wall and uterus. One of the factors for performing a cesarean section (CS) is breech presentation. Mothers who undergo cesarean section due to breech presentation require intensive care and monitoring. To reduce possible complications, postpartum mothers with this indication require monitoring in nursing care. To analyze nursing care for patients with Primigravida P1A0 in the Kalibiru Lor Ward of Wates Kulon Progo Regional General Hospital.  The research design used an observational case study with the research object obtained from 1 patient with Primigravida Breech Presentation in the Kalibiru Lor Ward of Wates Kulon Progo Regional General Hospital. This case had nursing diagnoses of acute pain, ineffective breastfeeding, and risk of falling. Nursing outcomes were pain level, breastfeeding status, and fall risk. Nursing interventions and implementation included pain management, breastfeeding education, and environmental fall prevention. Conclusion: Nursing care in this case resulted in the resolution of acute pain, effective breastfeeding, and the mitigation of fall risk.